1977
DOI: 10.1042/bj1630571
|View full text |Cite
|
Sign up to set email alerts
|

Properties and N-terminal sequence of allophycocyanin from the unicellular rhodophyte Cyanidium caldarium

Abstract: Allophycocyanin from the unicellular rhodophyte Cyanidium caldarium was purified by (NH4)2SO4 fractionation and ion-exchange chromatography on brushite (calcium phosphate) columns and on DEAE-Sephadex A-25 columns. The specific absorption coefficient (A0.1%1cm) at 650nm of purified allophycocyanin was 6.35 in 0.05M-potassium phosphate buffer, pH7.0. Absorption maxima of allophycocyanin occurred at 650, 618 (shoulder), 350 and 275 nm. Circular-dichroic spectra displayed positive-ellipticity bands at 658 and 630… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…This band is shifted to 625 nm and diminishes in intensity in pH 8.0 phosphate buffer, I 0.1. This spectrum is generally similar to those obtained with protein from either mesophilic or thermophilic algae (5,6).…”
Section: C-supporting
confidence: 63%
See 1 more Smart Citation
“…This band is shifted to 625 nm and diminishes in intensity in pH 8.0 phosphate buffer, I 0.1. This spectrum is generally similar to those obtained with protein from either mesophilic or thermophilic algae (5,6).…”
Section: C-supporting
confidence: 63%
“…At pH 7.0, the predominant 6S species was virtually completely converted to I I S hexamer in the presence of 2 M salt. At pH 6.0 no perturbation of 6S-1 1S equilibrium was noted, probably due to the initial presence of large amounts of hexamer (82% before the addition of salt). C-Phycocyanin solutions were dialyzed at pH 7.0 in the presence of a saturated benzene solution or 0.01 M phenol solution.…”
Section: C-mentioning
confidence: 99%
“…[17][18][19][20] Foguel and Weber 5 were also able to obtain subunits by the application of low temperature at high pressure, and they showed that the visible spectra of the subunits had a similar shape and maximum but much lower intensity than that of monomers. Schneider and coworkers 21 also studied spectral changes in biliproteins that were induced by high pressures.…”
Section: Subunits and Their Complex Behaviors In Reassociation Experimentioning
confidence: 95%
“…Native APC from Synechocystis sp. PCC 6803 was isolated on a brushite (CaHPO 4 Á2H 2 O) column, and further purified with a Superdex 200 size-exclusion column (Brown and Troxler 1977), and digested as above.…”
Section: Tryptic Digestion Of Apcmentioning
confidence: 99%